2D Numerical Modeling for Estimation of Run Up and Arrival Time of Tsunami at the Coast of Banyuwangi District - Alif Aulia Baroroh; Supriyadi; Sutikno; Mochamad Aryono Adhi; Hamzah Latief (Universitas Negeri Semarang, 2025)
The Banyuwangi tsunami was generated by an earthquake of magnitude 7.8 that struck the south coast of East Java with Mw 7.8 on June 3, 1994. The tsunami claimed the lives of more than 200 people, and severely damaged infrastructure, buildings and transportation facilities. Many studies have been conducted on the Banyuwangi tsunami, but not many have reviewed the validation of the maximum height compared to the results of field studies in the same year as the June 3, 1994 Banyuwangi tsunami. The study of Banyuwangi tsunami reconstruction aims to validate the maximum tsunami height of the model output compared to the results of field measurements by Tsuji in 1995. This study uses COMCOT v1.7 software with the nested model method. The results of the simulation of tsunami wave propagation that occurred every time period after the earthquake, showed that in snapshot layer 1 and layer 4 within 10 minutes the distribution of the earthquake expanded the tsunami wave propagation, within 30 minutes the tsunami wave propagation had entered several areas of the southern coast of East Java, within 35 minutes the tsunami wave propagation had reached land. The comparison ratio between model results and field measurements is K of 0.811998002 and